Draft Special Component Plan 1987-88 Government of Pondicherry - Planning Commission (Planning Commission, 1987)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast about 160 Kms. south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of south Arcot District of Tamil Nadu. Karaikal region is surrounded by Thanjavur District of Tamil Nadu.
Union Territory of Pondicherry